2017
DOI: 10.1002/dc.23685
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of well‐differentiated squamous cell carcinoma from non‐neoplastic oral mucosal lesions: New cytopathologic evaluation method dependent on keratinization‐related parameters but not nuclear atypism

Abstract: Recognition of the present five parameters is useful for oral SCC cytology. Diagn. Cytopathol. 2017;45:406-417. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Their narrow cytoplasm with sharply demarcated cell margins becomes deeply stained and has a glittering appearance. Although we previously described keratoglobules as not derived from keratin pearls but from single cell keratosis scattered in oral SCC/CIS foci [7], the present study, which examined an approximately four times greater number of SCC/CIS specimens, showed keratoglobules generated also within keratin pearls. Mohanta et al [19] reported "small keratinized round cells" as evidence of malignancy in oral cytology.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Their narrow cytoplasm with sharply demarcated cell margins becomes deeply stained and has a glittering appearance. Although we previously described keratoglobules as not derived from keratin pearls but from single cell keratosis scattered in oral SCC/CIS foci [7], the present study, which examined an approximately four times greater number of SCC/CIS specimens, showed keratoglobules generated also within keratin pearls. Mohanta et al [19] reported "small keratinized round cells" as evidence of malignancy in oral cytology.…”
Section: Discussioncontrasting
confidence: 81%
“…Among the five parameters of FPS, concentric arrangement of orangeophilic cells (parameter i) and keratoglobules (iv) were reconfirmed in the present study as highly characteristic and specific to oral malignancy, as they were exclusively found in malignant specimens, while not-definitely malignant specimens possessed none of them. Concentric arrangement of orangeophilic cells (i) represents small keratin pearls, probably in the initial phase [7]. In our previous studies, it was demonstrated that round-shaped dyskeratotic foci (small keratin pearls) in oral CIS are initiated from collapsed intraepithelial blood vessels [15, 17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This methodology, however, is not indicated to examine oral cytopathological samples due toits poor diagnostic accuracy in oral tissues. The cytoplasmic morphological characteristics recently described by Hara et al should be included as a new parameter to increase the accuracy of this preventive diagnostic method for OSCC. In this regard, the absence of a cytological sample of normal tissue from the same patient is a limitation of this report, as cytopathological results are known to present individual variations within normal standards.…”
Section: Discussionmentioning
confidence: 99%